A study of long wave run-ups on a bi-linear beach slope induced by solitary and transient-focused wave group. Issue 2 (3rd April 2019) - Ko, Haeng Sik; Lynett, Patrick J.
ABSTRACT: This paper presents long wave run-ups and rundowns on a bi-linear slope beach detected by using an image processing technique. For long wave run-ups, solitary wave run-up is obtained through experimental tests by Hydraulic-Control Wave-maker (HCW) and the dataset are validated by comparing Open-Source field Operation and Manipulation (OpenFOAM) with Reynolds Averaged Navier-Stokes (RANS)-type model and COrnell University Long and intermediate WAVE modelling package (COULWAVE) with Boussinesq-type model. For infragravity wave run-up, furthermore, a transient-focused wave group are generated and validated by the comparison of the numerical simulations. The results present not only that a low-frequency waves are enhanced by shoaling and breaking processes due to the bi-linear slope beach compare to the analytical solution on plane beach but that the series of wave run-ups are dominant by the low-frequency wave induced by the transient-focused wave groups.